Using dextran of different molecular weights to achieve faster freeze-drying and improved storage stability of lactate dehydrogenase. (16th March 2019) - Larsen, Bjarke Strøm; Skytte, Jeppe; Svagan, Anna J.; Meng-Lund, Helena; Grohganz, Holger; Löbmann, Korbinian
Abstract: Freeze-drying of protein formulations is frequently used to maintain protein activity during storage. The freeze-drying process usually requires long primary drying times because the highest acceptable drying temperature to obtain acceptable products is dependent on the glass transition temperature of the maximally freeze-concentrated solution ( Tg ′). On the other hand, retaining protein activity during storage is related to the glass transition temperature ( Tg ) of the final freeze-dried product. In this study, dextrans with different molecular weight (1 and 40 kDa) and mixtures thereof at the ratio 3:1, 1:1, and 1:3 (w/w) were used as cryo-/lyoprotectant and their impact on the stability of the model protein lactate dehydrogenase (LDH) was investigated at elevated temperatures (40 °C and 60 °C). The dextran formulations were then compared to formulations containing sucrose as cryo-/lyoprotectant. Because of the higher Tg ′ values of the dextrans, the primary drying times could be reduced compared to freeze-drying with sucrose. Similarly, the higher Tg and Tg ′ of dextrans relative to sucrose led to benefits during storage which was shown through improved protection of LDH activity.